A comparative study between Islamic financing system & conventional financing system with regards to the issue of property purchasing in Malaysia / Nur Katrina Mohamed Razif and Norliyana Abdul Manaf - Mohamed Razif, Nur Katrina; Abdul Manaf, Norliyana (2007)
Basically this study was initiated after realising that there are differences between the Islamic financing system and conventional financing system on the issues and problems regarding the sale/loan transactions given by both institutions when a purchaser/borrower wants to acquire any property or goods. It began with a proposal which was submitted and approved by the lecturer of the subject of Legal Research and Methodology. This study will specifically look into whether the rights of both the property purchasers and the Islamic-based bank or conventional bank will be balanced when there has been a default of payment on the part of the purchaser/borrower regarding the sale/loan agreement. The study shall also include a compilation of data and information regarding the issue. Through this study, it was found that the Malaysian public in general are not aware of the differences of both systems in the event of default of payment by the purchaser/borrower. At the end of the study, it can be concluded that both Islamic and conventional financing system has its own pros and cons with regard to safeguarding the rights of both the bank and the customers on the issue of property purchasing in Malaysia.